Fatty Food Consumption and Stroke Risk Among Older Adults in Indonesia: Analysis of the 2023 Indonesian Health Survey - Yuni Asri; Priasmoro, Dian Pitaloka; Nuris Kushayati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
In Indonesia, stroke is the leading cause of illness and death among the elderly. Dietary habits, especially fatty food intake, have been identified as changeable risk factors. Nonetheless, there is a scarcity of national data on this relationship among older Indonesian adults. This study sought to investigate the relationship between fatty food intake and stroke occurrence in elderly Indonesians, utilizing data from the 2023 Indonesian Health Survey (Survey Kesehatan Indonesia or SKI). This cross-sectional study was performed using secondary data from SKI 2023, encompassing 97,339 participants aged 60 years and above. The primary outcome was whether a stroke diagnosis was present (yes/no) and the key independent variable was the consumption of fatty foods (yes/no). Additional variables considered were age, gender, education, marital status, employment, residence, and alcohol use. Weighted descriptive statistics, chi-square tests, and binary logistic regression were conducted using STATA 14.1, with sampling weights applied. The stroke prevalence among elderly participants was 3.2%. The bivariate analysis revealed a significant association between fatty food consumption and stroke (p < 0.001). Multivariate logistic regression showed that elderly individuals who avoided fatty foods had a notably reduced risk of stroke (OR = 0.51, 95% CI: 0.45–0.58, p < 0.001). Alcohol consumption also had a protective effect (OR = 0.22, 95% CI: 0.12–0.43, p < 0.001). There is a significant association between fatty food consumption and stroke among the elderly population in Indonesia. Public health strategies encouraging healthier eating habits could potentially lower the stroke risk in this susceptible group